IMPROVING STUDENTS' VOCABULARY THROUGH WORDS MAPPING STRATEGY AT SMP NEGERI 6 TONDANO - Jane Sarah Marianca; Nihta V. F Liando; Agustine Clara Mamentu (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
English is an international language or number one language in the world. In Indonesia, English is considered as a foreign language (EFL), because English is rarely found in the daily communication of Indonesian people. This research aims to find out whether words mapping strategy is effective in improving students’ vocabulary or not. This research was conducted at ninth grade students of SMP Negeri 6 Tondano in academic year 2021/2022. In term of research, this research was quantitative research through pre-experimental design one group pre-test and post-test by using mean score formula. The research instrument was used in two forms that are multiple choice and true-false test. This test was intended to measure students’ vocabulary. The data were collected through descriptive text in form multiple choice and true-false test. Data were collected twice, before the treatment (pre-test) and after the treatment (post-test). The result of this research showed that the mean score of post-test Y = 81.60 was higher than the mean score in the pre-test  And result 7of standard deviation of Pre-test (Sdx) = 4.94 and standard deviation of Post-test (Sdy) = 4.59. It means that student achievement in vocabulary in the post-test after treatment is higher than these of the pre-test. From this result, the researcher put the conclusion that the application of words mapping strategy effectively improves students’ vocabulary. It Is recommended that improving vocabulary through words mapping strategy can be useful and help the ninth grade students of SMP Negeri 6 Tondano